Key characteristics of palliative care integration in intensive care units: A scoping review - King, Yvonne; Brady, Anne-Marie (My University, 2026)
Background: Intensive care units (ICUs) are increasingly managing patients with greater clinical complexity and life-limiting conditions. Systematic review evidence highlights that early palliative care, integrated alongside active treatment and not solely at end-of-life, can significantly improve outcomes for both patients and their families. Despite evidence on the effectiveness of palliative care integration models in the ICU setting, the specific characteristics for integration remain poorly articulated and insufficiently understood. Objectives: To systematically map key characteristics of palliative care integration models in adult ICUs. Eligibility criteria: We included integration models/frameworks for palliative care in adult ICUs and excluded studies that reported on stand-alone interventions. We limited the search to studies published from 2015, without restriction on study design or geographic location, to ensure a broad and inclusive review of global evidence. Sources of evidence: A comprehensive search was performed in July 2024 across six data bases: PsycINFO, CINAHL, Excerpta EMBASE, Cochrane Library, MEDLINE, and Web of Science in July 2024. The keywords ‘palliative care’ and ‘intensive care unit’ were used to identify literature on palliative care integration in ICU. Charting Methods: A data extraction table was used to extract relevant information from the included original research and review articles. Data were analysed using thematic analysis approach. Results: We screened 10,262 titles/abstracts, read 980 full-text articles, and ultimately included 60 publications in the final analysis. Thirty-five were original research studies and 25 were review articles, including four systematic reviews. Most research studies originated from the United States (n = 32), with one study each from India, Canada, and Singapore. We identified four key characteristics essential for integrating palliative care in the ICU including: 1. Screening criteria: structured tools to identify patients who may benefit from early palliative care alongside ongoing treatment. 2. Embedded daily practices: routines focused on symptom assessment, timely family meetings, and proactive palliative needs evaluation. 3. Education and training: targeted programs to strengthen ICU clinicians’ understanding of palliative care beyond end-of-life. 4. Specialist palliative care collaboration: joint rounding, embedded palliative nurse practitioners, and coordinated teamwork between ICU and specialist palliative care teams. Facilitators included embedding education in daily ICU practice and system-wide alignment, while barriers included limited clinician knowledge and the perception of palliative care as end-of-life only.
PUBLISHED
Keywords: Critical Care; End-of-Life Care; Intensive Care Units; Palliative Care; Scoping Reviews; Ageing; Cancer; International Development; Acute care nursing; Care of relatives within palliative care; Clinical : Critical Care Nursing / Decision Making; Critical Care; Evaluating health care interventions; Health Care Policy; Integrated Care; Palliative care; Palliative care nursing; Systematic reviews and meta analyses; Other; Policy